Utilization of estimated rainfall as an early warning system before flash flood event - Fara Diva Claudia; Cecylia Putri Mawarni; Kadek Krisna Yulianti; Paulus Agus Winarso (Journal of Physics: Theories and Applications, 2018)
On October 10, 2018 there has been extreme weather in the form of heavy rain accompanied by lightning in Tanah Datar District, West Sumatra. This extreme weather caused flash floods and landslides that killed many people. Therefore, by using remote sensing data in the form of radar and satellite as well as WRF modeling (Weather Research and Forecasting) the authors conducted analysis of heavy rainfall events to determine the estimated rainfall and atmospheric dynamics during the occurrence of flash floods and landslides. WRF modeling is used to determine the condition of atmospheric lability. For the calculation of rainfall estimation, the method used is the Convective Stratiform Technique (CST) method that utilizes satellite data and the Z-R relation selection method that utilizes radar data. Then the calculation results from each method are verified using observation data. Relative bias shows the CST method and the selection of Z-R relations tend to be overestimate, but has a very high correlation value with observation data. Information on rainfall estimation and atmospheric dynamics is expected to be used to provide early warnings aimed at minimizing losses from the impact of disasters.